2021
DOI: 10.3390/app11135773
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Localization of Multiple Damages through Entropy in Information Theory

Abstract: According to recent works, entropy measures, and more specifically, spectral entropies, are emerging as an efficient method for the damage assessment of both mechanical systems and civil structures. Specifically, the occurrence of structural system alterations (intended in this work as stiffness reduction) can be detected as a localized change in the signal entropy. Here, the Wiener Entropy (also known as the Spectral Flatness) of strain measurements is proved as a viable tool for single and multiple damage as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…For instance, in the two case studies mentioned earlier [10,11], the Shannon spectral entropy (SSE) was proven to be the most appropriate definition for masonry structures. Instead, for applications where mainly metallic components are utilised, the authors of [12,13] suggested the use of the Wiener entropy (WE) due to its higher sensibility to damage (in non-homogeneous materials, such as concrete or masonry, this higher sensibility to local inhomogeneities may cause false alarms).…”
Section: Motivations For Entropy-based Shmmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the two case studies mentioned earlier [10,11], the Shannon spectral entropy (SSE) was proven to be the most appropriate definition for masonry structures. Instead, for applications where mainly metallic components are utilised, the authors of [12,13] suggested the use of the Wiener entropy (WE) due to its higher sensibility to damage (in non-homogeneous materials, such as concrete or masonry, this higher sensibility to local inhomogeneities may cause false alarms).…”
Section: Motivations For Entropy-based Shmmentioning
confidence: 99%
“…The WE, being more sensitive to both structural and non-structural changes, was contrariwise suggested for metallic structures, with more uniform construction materials and fewer nonuniformities [12]. This allows us to take advantage of its major sensitivity with fewer false positives [12,13].…”
Section: Wiener Entropymentioning
confidence: 99%
“…Spectral entropy has been applied for rotary machinery as well; e.g., for the performance degradation assessment of rolling element bearing by Ref [16]. However, for such application where mainly metallic components are utilised, the Wiener Entropy (WE) should be preferred due to its higher sensibility to damage, which is apter for more homogeneous construction materials [17,18]. Therefore, different entropy definitions may apply more or less conveniently to different construction materials.…”
Section: Entropy Measurements and Their Application For Shmmentioning
confidence: 99%
“…The WE, being more sensitive to both structural and nonstructural changes, was contrariwise suggested for metallic structures, with more uniform construction materials and fewer nonuniformities [17]. This allows taking advantage of its major sensitivity with fewer false positives [17,18].…”
Section: Wiener Entropymentioning
confidence: 99%
“…Due to the influence of complex operating conditions and environment, the collected vibration signals of the rolling bearing are usually non-stationary and non-linear [20]. Many non-linear dynamic methods, such as sample entropy [21], permutation entropy [22], fuzzy entropy [23], Rényi entropy [24], Wiener entropy [25], Instantantaneous Spectral Entropy [26], dispersion entropy [27], are proposed, which can reflect the non-linear properties of vibration signal and characterize equipment health status. Sample Entropy is slow in calculating long time series, poor in real-time performance, and prone to a sudden change in similarity measurement [28].…”
Section: Introductionmentioning
confidence: 99%